Choosing a Virtual World Platform for Teaching: "VICERO" – A Scoring Model Aiding the Right Choice - Erenli, Kai (International Journal of Advanced Corporate Learning (iJAC), 2012)
When asking which Virtual World to use for educational purposes, people most often want to hear a one- sentence answer. Frequently the question leads to a discussion that can be compared to a debate about religion: you cannot be too sure which side you will choose but you are easily doomed from the beginning if you pick the wrong side (or in this case, platform). To help educators pick the right Virtual World platform we have developed a Scoring Model and Criteria Catalogue which support choosing the most suitable platform for teaching purposes. Educators can use the Scoring Model to rate the criteria based on their respective demand. The Scoring Model will then suggest a Virtual World platform from a â??long listâ? and instruct the educator how to install/use/maintain the platform. Thus educators will not be left alone with their choice and will get a motivational hint where to start and where to seek support. The â??long listâ? is monitored and updated regularly so that selections are always up-to-date.